THE COACHING DISCIPLINE STUDENTS THROUGH MODEL OF HABITUATION IN DAARUT TAUHID BOARDING SCHOOL BANDUNG - 3Kokom Komalasari, Anisa Fitriani Dasim Budimansyah (Jurnal Civicus, 2014)
The research aimed to explore and analyze the data gained from the field concerning the habituation model applied to build student discipline in Daarut Tauhid Junior Secondary Boarding School. The analysis was done using qualitative approach with case study method. The results showed that: (1) The habituation model applied at Daarut Tauhid Junior Secondary Boarding School in building student discipline was aimed to create pious and well-mannered individuals; (2) The process of building student discipline through habituation was successfully implemented according to the curriculum specially designed by Daarut Tauhid Boarding School; (3) The well-disciplined attitudes of the students were observable during their classroom activities, extracurricular activities, and daily activities in the dormitory; and (4) Exemplary, consistency, good regulations, and cooperation from all parties became the supporting factors in building student discipline. Meanwhile, students’ varying characteristics, minimum infrastructure, and negative effects of the development of science and technology were the hindrances of the process of building student discipline at Daarut Tauhid Junior Secondary Boarding School Bandung.Keywords: Discipline, Model Habituation, Boarding School